Estudo das propriedades antiespasmódicas e miorrelaxantes do óleo essencial de Ocimum Micranthum em traquéias isoladas de ratos wistar - Pinho, Joao Paulo Melo de (2010)
The Ocimum. micranthum Willd. is a plant popularly known as “alfavaca-de-folha-miúda” or “estoraque” and is used in folk medicine to treat flu, colds, fever, cough, bronchitis, stomach and intestinal infections, ear infections and as stimulant and carminative. This study aimed to show the activity of its essential oil (EOOM) and of its main constituent, methyl cinnamate, in rat isolated trachea. It was shown that both the OEOM and methyl cinnamate (1-1000 µg/mL) did not change the basal tone, but they were able to reverse the contractile response induced by potassium chloride or carbachol with IC50 of 112 and 128.2 µg/mL (for EOOM) and 308 and 100 μg/mL (for methyl cinnamate), respectively. At 100 µg/mL, added before the contractile agent, EOOM attenuated maximal response to KCl in trachea from naïve rats. This effect did not occur when contraction was induced by carbachol in the presence of nitrendipine. Additionally, in animals subjected to an ovalbumin-sensitized model of asthma, EOOM was more active in challenged than in sensitized animals. In conclusion,th e myorelaxant and antispasmodic effects of the EOOM are due to its preferential action on voltage-operated calcium channels. Its major constituent, methyl cinnamte, appears to be involved in the pharmacological effects of the EOOM.